Safety perception in patients with advanced idiopathic Parkinson’s disease – a qualitative study - Pedrosa, Anna J.; van Munster, Marlena; Timmermann, Lars; Pedrosa, David J. (Frontiers in Aging Neuroscience, 2023)
Background A fundamental cornerstone of quality of healthcare is patient safety, which many people with life-limiting illnesses feel is being compromised. Perceptions of impaired safety are associated with the occurrence of psychological distress and healthcare utilization. However, little is known about how people with idiopathic Parkinson’s disease (iPD) perceive their own safety toward the end of life. The aim of our study was therefore to investigate factors that influence the perception of safety of patients with advanced iPD. Methods We conducted semi-structured interviews with a purposeful sample of 21 patients with advanced iPD. Participants were recruited at the neurology department of a tertiary care hospital in Germany between August 2021 and June 2022. Data were analyzed using reflexive thematic analysis. Results iPD-patients reported relevant impairment of their safety. While most participants expressed safety concerns based on the manifestation of disease, our analysis identified enablers and barriers to establishing safety in patients with advanced iPD, in 10 additional domains: relationship to the disease, informedness, self-perception, utilization of support and care structures, healthcare professionals and structures, treatment, social interaction, social security, spirituality, and environment. Conclusion This study provides new insights into safety perceptions of patients with advanced iPD, which extend well beyond the physical realm. The findings suggest that clinicians and policy makers should consider a holistic and multidisciplinary approach to assessing and improving patients’ safety taking into account the enablers and barriers identified in this study.